Toxic metals and bioelements: Combined oxidative stress effects on liver injury and thyroid hormone disruption in subjects from different areas of Erbil province - Mahdi Yassin Ahmed; Kamaran Abdoulrahman (Toxicology Reports, 2025)
In Iraq, particularly in Erbil city and Gwer road are deemed environmentally disadvantaged because of industrial pollutants and refinery activities. This study conducted 143 subjects from rural, urban, and industrial areas. The sera of subjects were taken for the analysis. The toxic metals and bioelements were assessed using ICP-MS, the oxidative stress parameters were determined via ELISA. For estimation of liver test biomarkers Kenza was used, and thyroid hormones were measured by Cobas. While their relationships were statistically analyzed. The results indicated that metals concentrations were markedly significantly increased in industrial areas, particularly for Fe 599.1 (723.9) μg/L and Mn 7.534 ± 8.793 μg/L. The median level of Cu 4082 (2824) μg/L in urban subjects is significantly lower than those of other areas. Markers for oxidative stress revealed considerably higher MDA in urban participants 1917 (1085) pg/mL, while SOD and CP exhibited significantly lower level in urban and industrial participants P-value (0.0001 and <0.0001) respectively. The liver tests revealed elevated ALT in urban and industrial participants, 29.06 ± 1.723 IU/L and 21.94 ± 1.162 IU/L, respectively. The ALP levels were significantly elevated in industrial participants (P-value <0.0001). The study found that industrial workers had significantly higher levels of TSH 2.209 ± 0.1032 μIU/L and low levels of T3 1.765 ± 0.0227 nmol/l compared to the rural individuals. Fe had positive correlations with ONOO-. and TSH (r = 0.2221, r = 0.2452). Furthermore, Cu showed positively correlated with Cp (r = 0.2967; p = 0.0068), AST (r = 0.2417; p = 0.0268) and ALB (r = 0.2187; p = 0.0457). This study shows that increased levels of hazardous metals and bioelements in industrial and urban areas cause oxidative stress, which has a significant impact on public health and causes a number of health problems, including liver injury and thyroid dysfunction.